Outcome of Assessment and Preparation for Patients Undergoing Anesthesia at Preoperative Clinic - บุญปถัมภ์, ยุพิน; ดาววิจิตร, จงกลนี; ไชยชมภู, อรุณีย์ (Journal of Health Science of Thailand, 2021)
Preoperative assessment and preparation for patients undergoing anesthesia at least one day prior to surgery aims to evaluate risk and plan for management of perioperative complications that may occur. The purpose of this study was to compare the postponement of surgery in Chiangrai Prachanukroh Hospital between preparation at preoperative clinic and visiting on one day prior to the surgery (standard preparation). The study was designed as a historical control efficacy research. There were three groups of patients: (1) the patients who received standard preparation group, (2) the patients who received preparation during the development of preoperative clinic group, and (3) the patients who received preparation in preoperative clinic group. The numbers of patients in each group were 2973, 1141 and 1298, respectively. The data on demographic characteristics and postponement due to improper preparation were collected retrospectively from August 2016 to April 2017 in the first group; prospectively from May to October 2017 in the second group; and retrospectively from November to December 2017 and prospectively from January to April 2018 in the third group. The data were analyzed by using frequency, percentage, t-test, exact probability test and logistic regression. It was found that there were differences among three groups in terms of sex, age, ASA classification, underlying disease and consultation. The rate of receiving preoperative preparation at least one day prior to surgery in each group was 72.2%, 99.6% and 100.0%, respectively; and the postponement rate was 0.2%, 2.4% and 1.2%, respectively. After adjustment the differences among groups, the authors found 29.3% increase of the rate of receiving preparation at least one day prior to surgery and 1.2% increase of postponement rate in the third group when compared to the first group. This might be due to the unavailability of the postponed case record system. However, the postponement rate in the third group was less than the second group. The authors suggested that if there was no constraint on human resource, patients undergoing anesthesia should be prepared and assessed at the preoperative clinic. In addition, increased preoperative assessment and preparation should be promoted for patients in all other departments.